FINISHING TEKNIK BATIK P ADA KERAJINAN KA YU DI SANGGAR KARY A MANUNGGAL - Martono, Martono; Suardana, Wayan; Hendri, Zulfi (Universitas Negeri Yogyakarta, 2005)
The object of this voucher program can publicity be reganded to de velop or enlarge batik technique finishing on wood craft. The more spesific objects ot this program are as follows: (1) To develop design of batik mo tives on wood craft, (2) To develop liquit wax application using electrical canting (drawing pen), (3) To develop color composed variation using